In depth comparative phenotyping of blood innate myeloid leukocytes from healthy humans and macaques using mass cytometry. Issue 10 (26th April 2017) - Elhmouzi‐Younes, Jamila; Palgen, Jean‐Louis; Tchitchek, Nicolas; Delandre, Simon; Namet, Inana; Bodinham, Caroline L.; Pizzoferro, Kathleen; Lewis, David J.M.; Le Grand, Roger; Cosma, Antonio; Beignon, Anne‐Sophie
Abstract: Comparative immune‐profiling of innate responses in humans and non‐human primates is important to understand the pathogenesis of infectious and chronic inflammatory diseases as well as for the preclinical development of vaccines and immune therapies. However, direct comparisons of the two species are rare and were never performed using mass cytometry. Here, whole‐blood‐derived leukocytes from healthy humans and cynomolgus macaques were analyzed with mass cytometry. Two similar panels of around 30 monoclonal antibodies targeting human markers associated with innate myeloid cells to stain fixed human and macaque leukocytes were constructed. To compare the circulating innate cells from the two primate species, an analysis pipeline combining a clustering analysis by the Spanning‐tree Progression Analysis of Density‐normalized Events (SPADE) algorithm with a two‐step hierarchical clustering of cells nodes and markers was used. Identical SPADE settings were applied to both datasets, except for the 20 clustering markers which slightly differed. A correlation analysis designed to compare the phenotypes of human and macaque cell nodes and based on 16 markers, including 15 shared clustering markers and CD19 for humans or CD20 for macaques, revealed similarities and differences between staining patterns. This study unique by the number of individuals (26 humans and 5 macaques) and the use of mass cytometry certainly contributes to better assess the advantages and limits of the use of non‐human primates in preclinical research. © 2017 International Society for Advancement of Cytometry